Zethus (Zethus) wileyi (Hymenoptera, Vespidae, Eumeninae), a new species with its own species-group - Lopes, Rogerio B.; Noll, Fernando B. [UNESP]; Stange, Lionel A. (Magnolia Press, 2017)
Zethus wileyi Stange sp. nov. (Panama) is described and a cladistic analysis is carried in order to determine the relationship between the new species and the other species in the hilarianus species-group. The new species is assigned to its own new species-group due to evident differences in the morphology.
Keywords: potter and mason wasps; phylogeny; new species-group; hilarianus species-group; Neotropic Region